Leveraging Health Analytics to Address Public Health Crises: A Comprehensive Analysis - Aliyuda, Christian (International Journal of Scientific Research and Management (IJSRM), 2022)
Public health crises, whether originating from pandemics, natural disasters, bioterrorism, or other emergent threats, present significant challenges to global health systems, necessitating rapid and organized responses. Health analytics, encompassing the application of data analytics, machine learning, and statistical models to health-related data, has emerged as an essential tool for predicting, managing, and mitigating the effects of such crises. In this article, we explore the evolving role of health analytics in addressing public health emergencies by leveraging real-time data, advanced modeling techniques, and large-scale information from various data streams. Health analytics enables public health officials to identify outbreaks earlier, optimize resource distribution, and improve communication strategies with the public. Additionally, we examine ethical considerations around data privacy, the quality of data sources, and challenges in low-resource settings. Through a critical analysis of key case studies, including the COVID-19 pandemic, we investigate how health analytics can revolutionize public health response frameworks, offering opportunities for more dynamic and responsive health systems. While the power of health analytics is profound, its potential is still hampered by infrastructural deficits, data-sharing issues, and significant ethical dilemmas that must be addressed to fully realize its capabilities.